Isolation of Bacteriophage Against the Drug Resistant Clinical Pathogens and Host Range Analysis - Khadka, Kundan; Chaturwedi, Shashi Bhusan; Malla, Rajani; Chaudhary, Richa (International Journal of Applied Sciences and Biotechnology, 2024)
Antibiotic crisis is a major challenge being encountered by the global population as a result of development of antibiotic-resistant bacteria. Thus, shifting the focus to explore alternative methods to treat bacterial infection. Bacteriophage, the natural predator of the bacteria is one of those alternatives. This study is aimed to isolate bacteriophages from different types of water samples which are capable of infecting drug-resistant clinical isolates and understand its host range capacity. The isolation of bacteriophage was done by Double Layer Agar Assay (DLAA) from 3 different water samples i.e sewage sample from Bagmati and ALKA hospital and from Lele river water. For the isolation of phage, host organisms used were Multi Drug Resistant (MDR) E. coli and K. oxytoca resistant to Amoxyclav, Cefotaxime, Ciproflaxcin, Erythromycin, and Nalidixic Acid. Phage against E. coli II was isolated from both sewage samples while K. oxytoca phage was isolated from Bagamti sewage only. Phage could not be isolated against E. coli I and K. oxytoca phage could not be sub cultured as no plaques were formed on sub culturing and it showed temperate properties. The host range analysis of E. coli II phage showed that the phage has narrow host range as it did not formed plaques against bacteria of other genera. This indicates that sewage is the best source for discovery of phage and the isolated bacteriophage are capable of lytic activity on MDR bacterial isolates. Even though the isolated bacteriophage has potential to be used in phage therapy, still further research should be done for its application. Int. J. Appl. Sci. Biotechnol. Vol 12(4): 201-206.